Review paperMadame Maria Sklodowska-Curie – brilliant scientist, humanitarian, humble hero: Poland’s gift to the World - Trombetta, Mark (Journal of Contemporary Brachytherapy, 2014)
In 1911, when the Nobel Foundation awarded its coveted Chemistry Prize to a 44 year old Polish born woman, it is likely they may not have expected the action ever duplicated in the more than 100 years that followed. In fact, it was the second Nobel Prize in the sciences awarded to Maria Sklodowska-Curie, whom the world would come to admire, know, and love as Madame Curie. In a time of science dominated by men, the diminutive in size but larger-than-life Curie would become the first women to be awarded the prize. To this date, she remains the only person in history to win two Nobel prizes in two different science fields, and only one of four persons to win more than one. In total, Mme. Curie and her immediate family would be awarded five Nobel prizes. As astonishing as these facts may be, Mme. Curie did not seek fame nor did she seek self aggrandizement. Her whole life was one of service to humanity, an indefatigable work ethic, and humility.